Cold molecular gas and free–free emission from hot, dust-obscured galaxies at z ∼ 3. Issue 2 (6th June 2020) - Penney, J I; Blain, A W; Assef, R J; Diaz-Santos, T; González-López, J; Tsai, C-W; Aravena, M; Eisenhardt, P R M; Jones, S F; Jun, H D; Kim, M; Stern, D; et al.
ABSTRACT: We report on observations of redshifted CO(1–0) line emission and observed-frame 30 GHz radio continuum emission from five ultra-luminous, mid-IR selected hot, Dust-Obscured Galaxies (Hot DOGs) at z3 using the Karl G. Jansky Very Large Array. We detect CO(1–0) line emission in all five Hot DOGs, with one of them at high signal-to-noise ratio. We analyse FIR-radio spectral energy distributions, including dust, free–free, and synchrotron emission for the galaxies. We find that most of the 115 GHz rest-frame continuum is mostly due to synchrotron or free–free emission, with only a potentially small contribution from thermal emission. We see a deficit in the rest-frame 115 GHz continuum emission compared to dusty star-forming galaxies and sub-millimetre galaxies (SMGs) at high redshift, suggesting that Hot DOGs do not have similar cold gas reserves compared with star-forming galaxies. One target, W2305−0039, is detected in the FIRST 1.4 GHz survey, and is likely to possess compact radio jets. We compare to the FIR–radio correlation, and find that at least half of the Hot DOGs in our sample are radio-quiet with respect to normal galaxies. These findings suggest that Hot DOGs have comparably less cold molecular gas than star-forming galaxies at lower, z2 redshifts, and are dominated by powerful, yet radio-quiet AGN.